How does culture affect the performance in Chinese companies - WANG, Ruotong (2016)
This study tries to seek and explore the relationship between culture and performance in Chinese business context. Therefore a comparative case study analysis was conducted by selecting Huawei and Alibaba, two top Chinese companies nowadays. Each company will be examined its organizational culture and the impacts of national culture. The result of research shows that strong culture theory by Peters and Waterman can have some reasons, while Barney’ s competitive advantage claim also affects and determines the performance of a company.